Cumhuriyet Devri Şiir Poetikası (1940-1950) - Avcı, İsmail (My University, 2014)
Poetika, şiir kadar eski olup şiirle beraber var olmuş bir kavramdır. Aristo’nun şiirin ilkelerini ele aldığı eserine ‘poetika' demesi ile beraber şiir tarihine giren kavram, zaman içinde farklı kültürlerde kendi yorumunu bularak günümüze kadar gelmiştir. Türk şiirinin poetik metinlerini ise, tezkirelerin ve divanların dibaceleri ile yeni dönemde önsözler, belagat kitapları ve şairlerin şiirlerinin içine serpiştirdikleri mısralar oluşturmaktadır. Bu tezin amacı, Cumhuriyet devri şiir poetikasında, 1940-1950 yılları arasında ideal bir şiirden ne anlaşıldığını belirlemek, bu doğrultuda şairin gelenek, toplum ve kendi “ben”iyle ilişkilerini irdeleyerek şairi, böyle bir şiir anlayışına iten dinamikleri tespit etmek ve bu ilişkilerin nedenselliğini irdelemektir. XX. yüzyıl, Türk şiiri için yenilenme, kabuk değiştirme yüzyılı olmuştur. Bu yüzyılda görülen yenileşme hareketleri ile birlikte sosyal ve edebî gelişmeler farklı üslup özellikleri, farklı karakterde şairlerin yetişmesine yol açmıştır. Bu bakımdan bu dönemin poetik ürünleri de çeşitlilik ve farklılık arz etmektedir.

Having been as old as poetry, poetics is a concept which has always existed along with poetry. Poetica being the coinage by Aristoteles and also the name of his work on the principles of poetiy. is an extant concept though slightly differing in various cultures because of some changes and interpretations they underwent in these cultures. The poetica texts in the history of Türk poetry make up the corpus of poetry strings the Türk poets spread throughout tezkires the preambles of divans with prologue, the rhetoric books and their poetiy of new age. The aim of this thesis is to determine what is meant by “an ideal poetrty in the Republic Period's poetry of 1940 - 1950, and in this light, to determine the dynamics that lead the poet to such an understanding by evaluating the poet's relationship to tradition, to society and to his own “self”, and then to elaborate on the causality of these relationships. The twentieth century was a time of change and innovation for the Türk poetry. Together with the innovative movements in this century new poets with social and literary developments and different characteristics appeared. Therefore the poetica output of this era is quite various and contrasting.
Keywords: 20. yy; Biyografiler; Şairler; Tarih ve Eleştiri; Türk Dili ve Edebiyatı; Türk Şiiri